Climate-smart policies for Indian agriculture - Padhee, Arabinda Kumar (Indian Farming, 2018)
The impact of climate change on the ‘complex and risk prone’ farming systems of India will be disastrous, if ‘climate-wise’ development policies are not implemented with focus and regularity. Farmers must gain access to the rich scientific knowledge recommended by various research institutions/projects through efficient dissemination of the climate-smart technologies. Moreover, agricultural practices which have smaller ecological footprints and capable of competitive economic returns should be promoted.Suitable policies and strategies(both adaptation and mitigation) in a changing climate can only be ignored at the cost of agricultural growth and economic development of India.